Synthesis, Purification and Modification of Poly(Methyl Methacrylate) Microspheres for Prosthetic Dental Applications (Journal of Research Updates in Polymer Science, 2025)
A large number of polymers are used for various applications in prosthodontics. Poly(methyl methacrylate) (PMMA) microspheres are commonly used for prosthetic dental applications, including the fabrication of artiﬁcial teeth, dentures, denture bases, obturators, orthodontic retainers, temporary or provisional crowns, and for the repair of dental prostheses. Obviously, one can find a lot of articles dedicated to PMMA synthesis. On the other hand, the materials used in prosthodontics are subject to very specific requirements. Thus, in this work, influence of all the stages of PMMA microspheres production (including synthesis and, especially, purification) on the polymers characteristics is detected.